2010
DOI: 10.1007/s10461-010-9855-0
|View full text |Cite
|
Sign up to set email alerts
|

Lower HIV Prevalence Among Asian/Pacific Islander Men Who Have Sex with Men: A Critical Review for Possible Reasons

Abstract: We conducted a critical literature review for possible reasons that may explain the lower HIV prevalence observed among API MSM compared to MSM of other races/ethnicities. Trends emerging from the literature suggest that traditional individual-level factors-unprotected anal intercourse, substance use, STD prevalence, rates and frequency of HIV testing, and utilization of HIV prevention services-do not appear to be related to the lower HIV prevalence among API MSM. Some evidence suggests that socio-cultural and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 89 publications
(173 reference statements)
0
19
0
Order By: Relevance
“…An overwhelming focus on deficits among gay and bisexual men predisposes prevention efforts to ignore the strong body of evidence for resilience that exists in this population [8,[12][13][14]; evidence that may be useful in designing interventions to address health disparities. This suggests that learning how strengths evolve could improve prevention efforts by capitalizing on the skills and resources that already exist among gay and bisexual men.…”
Section: A Critique Of Relying Only On a Deficit Approach To Public Hmentioning
confidence: 99%
“…An overwhelming focus on deficits among gay and bisexual men predisposes prevention efforts to ignore the strong body of evidence for resilience that exists in this population [8,[12][13][14]; evidence that may be useful in designing interventions to address health disparities. This suggests that learning how strengths evolve could improve prevention efforts by capitalizing on the skills and resources that already exist among gay and bisexual men.…”
Section: A Critique Of Relying Only On a Deficit Approach To Public Hmentioning
confidence: 99%
“…For example, some work has shown that men find Asian MSM less desirable as sex partners because they are perceived to be less masculine and more submissive. 18,19 This too has led to insularity, with many sex ties among Asian MSM being intraracial, 20 although within a population with significantly lower HIV prevalence. 1 Thus, further research into the methods by which MSM select partners may help our understanding of the spread of HIV within and between racial/ethnic communities.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical studies have emerged to investigate whether acculturation is associated with behaviors related to HIV infection or HIV risk reduction (Wei et al, 2011). Some previous reviews have examined immigrants’ HIV-related behaviors but have not focused on the impact of acculturation on sexual behaviors (Organista & Organista, 1997; Tosh & Simmons, 2007; Wei et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Some previous reviews have examined immigrants’ HIV-related behaviors but have not focused on the impact of acculturation on sexual behaviors (Organista & Organista, 1997; Tosh & Simmons, 2007; Wei et al, 2011). Two exceptions are the reviews conducted by Bradford et al (2002) and Afable-Munsuz and Brindis (2006).…”
Section: Introductionmentioning
confidence: 99%